Acidification and hypoxia drive physiological trade-offs in oysters and partial loss of nutrient cycling capacity in oyster holobiont - Hemraj, Deevesh Ashley; Falkenberg, Laura J.; Cheung, Khan; Man, Lauren; Carini, Alessia; Russell, Bayden D. (Frontiers in Ecology and Evolution, 2023)
Introduction Reef building oysters provide vast ecological benefits and ecosystem services. A large part of their role in driving ecological processes is mediated by the microbial communities that are associated with the oysters; together forming the oyster holobiont. While changing environmental conditions are known to alter the physiological performance of oysters, it is unclear how multiple stressors may alter the ability of the oyster holobiont to maintain its functional role. Methods Here, we exposed oysters to acidification and hypoxia to examine their physiological responses (molecular defense and immune response), changes in community structure of their associated microbial community, and changes in water nutrient concentrations to evaluate how acidification and hypoxia will alter the oyster holobiont’s ecological role. Results We found clear physiological stress in oysters exposed to acidification, hypoxia, and their combination but low mortality. However, there were different physiological trade-offs in oysters exposed to acidification or hypoxia, and the combination of stressors incited greater physiological costs (i.e., >600% increase in protein damage and drastic decrease in haemocyte counts). The microbial communities differed depending on the environment, with microbial community structure partly readjusted based on the environmental conditions. Microbes also seemed to have lost some capacity in nutrient cycling under hypoxia and multi-stressor conditions ( 50% less nitrification) but not acidification. Discussion We show that the microbiota associated to the oyster can be enriched differently under climate change depending on the type of environmental change that the oyster holobiont is exposed to. In addition, it may be the primary impacts to oyster physiology which then drives changes to the associated microbial community. Therefore, we suggest the oyster holobiont may lose some of its nutrient cycling properties under hypoxia and multi-stressor conditions although the oysters can regulate their physiological processes to maintain homeostasis on the short-term.